Curriculum Integration as a Learning Experience: A Roadmap for Its Implementation in Two Teacher Training Courses in the Area of Primary Education - Arguedas-Ramírez, Ana (2021)
Introduction. This article systematizes the experience of curricular integration, carried out in 2018 by the teachers of DBJ 402 Didactics of Sciences and Mathematics for Basic Education and DBJ 403 Child Development in I and II Cycle courses, of the Pedagogy career with an emphasis in I and II Cycle of the Basic General Education of the Basic Education Division (DEB). The process organization, its implementation, the teachers’ assessment, and the student perception are developed in this paper. Objective. To enrich student training and strengthen the objectives and topics of both courses. Method. The phases with the different actions carried out to implement the curricular integration are explained, implementing three strategies that favored the link between knowledge and learning, both for the teachers and the student group. As part of the systematization process of the experience, a questionnaire was applied to gather the students’ perceptions about the experience and determine the strengths and recommendations expressed by the students regarding the carried-out strategies. Analysis of results. Implementing this integrative practice required commitment, planning, and a new look at the teaching work by the university faculty, besides the active participation of students. Conclusions. Implementing these practices represents a challenge for university teachers.